Sustainable Churchill Discussion Paper - Distasio, Jino; Dudley, Michael; Mulligan, Susan; Town of Churchill Local Steering Committee (2015)
report: 71pp., ill., digital file. This Discussion Paper introduces the Sustainable Churchill initiative between the Town of Churchill and the University of Winnipeg. It provides an overview of major concepts, including what is meant by community sustainability, with the intention that area residents will be better able to participate at the upcoming “Community Visioning” and other engagement sessions from August 31st to September 2nd, 2009. The Discussion Paper is intended to help generate a more effective partnership between the residents of the Town and the University of Winnipeg, by giving all parties a starting point for discussion and planning. It will help set the foundation for Churchill’s Sustainability Plan. Omnitrax Inc.